Synthesis, characterization, in vitro antimicrobial and cytotoxic studies of Co(II), Ni(II), Cu(II), and Zn(II) complexes obtained from Schiff base ligands of 1, 2, 3, 4‐tetrahydro‐naphthalen‐1‐ylamine. (14th June 2022) - Devi, Jai; Sharma, Som; Kumar, Sanjeev; Kumar, Binesh; Kumar, Deepak; Jindal, Deepak Kumar; Das, Souvik
Abstract : The transition metal complexes of Co(II), Ni(II), Cu(II) and Zn(II) with bidentate Schiff base ligands (HL 1−5 ) were obtained from condensation of 1, 2, 3, 4‐tetrahydro‐naphthalen‐1‐ylamine with methanolic solution of 3‐hydroxy‐salicylaldehyde, 4‐hydroxy‐salicylaldehyde, 5‐bromo‐salicylaldehyde, 3, 5‐dibromo‐salicylaldehyde, and 2‐hydroxy‐1‐napthaldehyde. The synthesized compounds were structurally elucidated by spectral and physical methods. The spectral characterization emphasized bidentate nature (NO) of Schiff base ligands which gets chelated with metal via nitrogen atom of imine group and deprotonated oxygen of salicylaldehyde/2‐hydroxy‐1‐napthaldehyde group to form octahedral geometry around metal atom. Thermal results supported that the complexes are stable upto 200°C leaving metal oxide as an end products. The reported compounds (1 –25 ) in this series were screened against the bacterial strains, that is, two Gram positive: Bacillus subtilis and Staphylococcus aureus, two Gram negative: Pseudomonas aeruginosa and Escherichia coli, and two fungal strains: Candida albicans and Aspergillus niger and their results that indicated moderate to good activity with compounds 20 and 21 having good antimicrobial activity (minimum inhibitory concentration [MIC] value 0.0269–0.0067 μmol/ml) as compared with control drugs ciprofloxacine and fluconazole. Furthermore, cytotoxic studies of synthesized compounds were carried out against three human cancer cell lines: HCT‐116 (colon), A549 (alveolar), and MCF‐7 (breast) using standard drug paclitaxel. The results demonstrated that compounds 1 (IC50 values = 12.93, 15.13, 17.24), 3 (11.9, 9.29, 12.64), 9 (17.06, 20.06, 22.87), 14 (16.21, 18.47, 20.00), and 25 (17.54, 17.21, 20.23) for three cancer cell lines were found to be most potent candidates among the synthesized compounds. Abstract : The synthesized compounds (1 –25 ) were screened for in vitro cytotoxicity against HCT‐116 (colon), A549 (alveolar), and MCF‐7 (breast) human cancer cell lines. Zinc complex (25 ) was found to be the most active antitumor agent.